Methodological Trends in Secondary Education and Transition Research: Looking Backward and Moving Forward. (May 2013) - Carter, Erik W.; Brock, Matthew E.; Bottema-Beutel, Kristen; Bartholomew, Audrey; Boehm, Thomas L.; Cease-Cook, Jennifer
Prevailing policy and practice in the field of transition emphasizes the importance of designing services and supports based on research-based practices. We reviewed every article published across the 35-year history of Career Development and Transition for Exceptional Individuals (CDTEI) to document methodological trends in research focused on equipping youth and young adults with disabilities for adulthood. Although experimental research articles have assumed increasing prominence within the journal since the late 1980s, the vast majority of published studies could be characterized as primarily descriptive in focus. While almost one quarter of research articles involved some type of intervention evaluation, only 25 studies reported using research designs that could allow causal claims to be made. The data collection approaches used in these studies were quite diverse, with self-report surveys and questionnaires representing the dominant approach. We summarize the current methodological legacy of CDTEI and offer some modest recommendations for where the field might go next in its efforts to conduct rigorous research that enables youth with disabilities to flourish.